2006
DOI: 10.1051/0004-6361:20054606
|View full text |Cite
|
Sign up to set email alerts
|

Globular cluster systems of six shell galaxies

Abstract: Context. Shells in Elliptical Galaxies are faint, sharp-edged features, believed to provide evidence of a recent (∼0.5−2 × 10 9 years ago) merger event. We analyse the Globular Cluster (GC) systems of six shell elliptical galaxies, to examine the effects of mergers upon the GC formation history. Aims. We examine the colour distributions, and investigate differences between red and blue globular cluster populations. We present luminosity functions, spatial distributions and specific frequencies (S N ) at 50 kpc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 109 publications
13
43
0
Order By: Relevance
“…The background-corrected histograms reveal that most of the GC candidates with colors (g − i ) 0 0.7 can be accounted for as part of the contamination, except for NGC 2865 and especially NGC 4240, where a significant number of blue sources remain. The blue population in NGC 2865 is consistent with the results of Sikkema et al (2006), who proposed the existence of a population of young clusters. Visually, the clearest case for bimodality can be seen in the IC 4889 color histogram, which contradicts the result of Gebhardt & Kissler-Patig (1999), who found no evidence of bimodality in the GCS of this galaxy.…”
Section: Gc Color Distributionsupporting
confidence: 90%
See 2 more Smart Citations
“…The background-corrected histograms reveal that most of the GC candidates with colors (g − i ) 0 0.7 can be accounted for as part of the contamination, except for NGC 2865 and especially NGC 4240, where a significant number of blue sources remain. The blue population in NGC 2865 is consistent with the results of Sikkema et al (2006), who proposed the existence of a population of young clusters. Visually, the clearest case for bimodality can be seen in the IC 4889 color histogram, which contradicts the result of Gebhardt & Kissler-Patig (1999), who found no evidence of bimodality in the GCS of this galaxy.…”
Section: Gc Color Distributionsupporting
confidence: 90%
“…It presents a remarkably steep age gradient from a central ∼1.5 Gyr (Sánchez-Blázquez et al 2007;Reda et al 2007) to ∼10 Gyr close to 1R e ; it also has a steep metallicity gradient (Reda et al 2007). Its GCS was studied by Sikkema et al (2006) using HST/ACS, finding a sizeable blue population consistent with a young-to-intermediate GC population (see also Trancho et al 2014). -NGC 3962 is part of the sample of Smith et al (2004) of field ellipticals without companions, as confirmed by Madore et al (2004), and no signs of any tidal disturbance (Tal et al 2009).…”
Section: Galaxy Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies also support this formation scenario (e.g. Whitmore et al 1993;Sikkema et al 2006;Trancho et al 2014).…”
Section: Introductionmentioning
confidence: 73%
“…Since the seminal review by Harris & Racine (1979) an enormous amount of work has been devoted to GCS identification in external galaxies and study of their properties. Regarding the GCS radial profiles, we recall, for the sake of example, recent papers of Bassino et al (2006), Goudfrooij et al (2007), Lee et al (2008), Rhode et al (2007), Sikkema et al (2006), Spitler et al (2006), Spitler et al (2008), Rhode & Zepf (2003), Peng et al (2004) and Harris et al (2009).…”
Section: Introductionmentioning
confidence: 99%